Temperature detection system for individual with congenital insensitivity to pain with anhidrosis. - Banerjee, Saikat Pinaki (My University, 2019)
The integration of temperature sensors into a sensing array is highly desirable for the development of wearable technologies. Here we describe an array of cost-effective temperature-sensitive resistors integrated into a glove apparatus to monitor ambient temperature in addition to the thermal changes of objects, to analyze temperature on contact while facilitating the handling of hot objects. The contact measurement system reflects the change in resistance, which varied linearly with temperature. The resistance signal is converted into a conditioned voltage using an amplification that supplies a constant current source. The digital signal is fed into a temperature-resistance mapping function for sensed temperature determination, which is then transmitted using a wireless module to the MQTT server via adafruit IO to the wireless device. Sudden changes in an object's temperature are easily detectable, wherein an alarm is activated to inform the end user. The temperature-sensitive resistor exhibited good accuracy and repeatability over a linear dynamic range of 30 °C to 200 °C with an average temperature coefficient of resistivity (TCR) of 0.0011/ °C with a high correlation coefficient.